2012
DOI: 10.3109/09537104.2012.674165
|View full text |Cite
|
Sign up to set email alerts
|

The effect of metformin on mean platelet volume in dıabetıc patients

Abstract: Diabetes mellitus (DM) is an independent risk factor for cardiovascular diseases. Metformin, the most commonly used antidiabetic, also has an antiatherogenic effect. Mean platelet volume (MPV) is increased in patients with high thrombogenic activation and also at risk for atherosclerosis. The purpose of this study was to examine the effects of metformin on MPV values in newly diagnosed type II DM patients on metformin monotherapy. In this study, 60 newly diagnosed type II DM patients (45 females, 15 males), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
45
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 15 publications
2
45
1
1
Order By: Relevance
“…[6] Metformin, which has been shown to exhibit antiatherogenic effect by decreasing cholesterol levels, inflammatory markers and vascular adhesion molecules, decreased MPV values. [11] Other studies showed higher MPV among type 2 DM patients who had microvascular complications (retinopathy or microalbuminuria). [5] The large platelets contain more dense granules, are more potent than the smaller platelets, and are hence more thrombogenic.…”
Section: Discussionmentioning
confidence: 94%
“…[6] Metformin, which has been shown to exhibit antiatherogenic effect by decreasing cholesterol levels, inflammatory markers and vascular adhesion molecules, decreased MPV values. [11] Other studies showed higher MPV among type 2 DM patients who had microvascular complications (retinopathy or microalbuminuria). [5] The large platelets contain more dense granules, are more potent than the smaller platelets, and are hence more thrombogenic.…”
Section: Discussionmentioning
confidence: 94%
“…79 It was also demonstrated that values of MPV were significantly higher in patients on oral hypoglycemic therapy than patients on insulin treatment. 80 Although insulin treatment was shown to decrease the activation and expression of cytokines, in a study neither insulin nor metformin was shown to reduce inflammatory marker levels such as hs-CRP and IL-6.…”
Section: Discussionmentioning
confidence: 98%
“…Briefly, the most commonly used glucose-lowering drugs like metformin, sulphonylureas (e.g. glimepiride, gliclazide, gliquidone and glibenclamide) and insulin, have all been shown to exert beneficial effects on platelets [1,[7][8][9][10][11]. Among the relatively more recent drugs, there is evidence for glucagon-like peptide-1 receptor agonists, glitazones and other classes of drugs [10,12].…”
mentioning
confidence: 97%